Development of an encyclopedia of flora and fauna motifs in Singkawang hand-written batik as a biology learning resource - Perabela Ramanda; Mahwar Qurbaniah; Anandita Eka Setiadi (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Singkawang City has biodiversity that inspires motifs in Singkawang batik. In order to introduce batik tulis in the city of Singkawang, an encyclopedia media was developed on biodiversity material. This study aims to develop an encyclopedia of flora and fauna motifs of Singkawang hand-written batik by measuring the level of validity and student response to the encyclopedia. This research uses the R&D method with the 4D development model, which consists of defining, designing, developing, and disseminating. Data collection using interviews, observations, questionnaires, and documentation, analyzed with descriptive techniques. The results showed the average validation score in the very valid category, in the media aspect (98.81%), material aspect (98.25%) and language aspect (84.72%). The media was considered practical with very strong criteria based on student responses with an average of 88.78% in the small-scale trial and 96.57% in the large-scale trial. It is concluded that the encyclopedia media of flora and fauna motifs of Singkawang hand-written batik is very valid and very strong from students. The existence of this encyclopedia media is expected to increase public knowledge, especially the younger generation in Singkawang City about the flora and fauna motifs of Singkawang hand-written batik, so that they are able to maintain and preserve hand-written batik in Singkawang city.Abstrak. Kota Singkawang memiliki keanekaragaman hayati yang menginspirasi motif pada batik tulis Singkawang. Demi memperkenalkan batik tulis yang ada di kota Singkawang maka di kembangkan media ensiklopedia pada materi keanekaramanan hayati. Penelitian ini bertujuan untuk mengembangkan ensiklopedia corak motif flora dan fauna batik tulis Singkawang dengan mengukur tingkat kevalidan dan respon siswa terhadap ensiklopedia. Penelitian ini menggunakan metode R&D dengan model pengembangan 4D, yang terdiri dari pendefinisian, perancangan, pengembangan, dan penyebaran. Pengumpulan data menggunakan wawancara, observasi, angket, dan dokumentasi, dianalisis dengan teknik deskriptif. Hasil penelitian menunjukkan rata-rata nilai validasi pada kategori sangat valid, pada aspek media (98,81%), aspek materi (98,25%) dan aspek bahasa (84,72%). Media tersebut dinilai praktis dengan kriteria sangat kuat berdasarkan respon siswa dengan rata-rata 88,78% pada uji coba skala kecil dan 96,57% pada uji coba skala besar. Disimpulkan bahwa media ensiklopedia corak motif flora dan fauna batik tulis Singkawang sangat valid dan sangat kuat dari siswa. Adanya media ensiklopedia ini diharapkan menambah pengetahuan masyarakat khususnya generasi muda di Kota Singkawang mengenai corak motif flora dan fauna batik tulis Singkawang, sehingga mampu menjaga dan melestarikan batik tulis yang ada di kota Singkawang.